2015
DOI: 10.3389/fpls.2015.00886
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Breeding Strategy and Challenges Towards Improvement of Blast Disease Resistance in Rice Crop

Abstract: Rice is a staple and most important security food crop consumed by almost half of the world’s population. More rice production is needed due to the rapid population growth in the world. Rice blast caused by the fungus, Magnaporthe oryzae is one of the most destructive diseases of this crop in different part of the world. Breakdown of blast resistance is the major cause of yield instability in several rice growing areas. There is a need to develop strategies providing long-lasting disease resistance against a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
99
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 119 publications
0
99
0
3
Order By: Relevance
“…Backcrossed plants in our study deviated from epistasis and the independent model. However, Ashkani et al (2015) reported that a dominant epistatic interaction exists in PS2, using pathotype P5.0 with an F 3 population. This suggests the presence of two independent dominant genes that result in epistatic effects of multiple loci with major and minor resistance genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Backcrossed plants in our study deviated from epistasis and the independent model. However, Ashkani et al (2015) reported that a dominant epistatic interaction exists in PS2, using pathotype P5.0 with an F 3 population. This suggests the presence of two independent dominant genes that result in epistatic effects of multiple loci with major and minor resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Four dominant genes at different loci were identified against the most virulent pathotype of M. oryzae Tanweer et al, 2015a). In addition, Ashkani et al (2015) reported an epistatic effect in a study including two different races of fungus. Extensive information about host resistance as well as the pathogen are essential to develop new rice varieties with long-lasting blast resistance and a broad range of resistance consisting of both qualitative and quantitative genes (Padmavathi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Rice blast is caused by the ascomycetous fungus Magnaporthe oryzae , which is one of the most serious and devastating epiphytic diseases in rice production worldwide (Ashkani et al, 2015). Currently, more than 24 major R genes conferring resistance to M. oryzae have been identified in rice, including Pi-ta (Jia et al, 2016), Pi-k (Wu et al, 2014), and Pb1 (Inoue et al, 2013), and modulation of these R genes significantly maintains and improves the grain yield and quality in modern rice cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…However, resistance breakdown following adaptation of the fungus has frequently been observed (Ou 1985) and breeding durably resistant rice cultivars remains a challenge. Molecular breeding approaches facilitate the identification and deployment of resistance genes (Ashkani et al 2015) and effective and durable resistance would be best achieved by combining both quantitative and qualitative resistance (Ballini et al 2008; Boyd et al 2013). …”
Section: Introductionmentioning
confidence: 99%